Students’ Motivation in Studying English: a Case Study at The Eleventh Grade Students MA Kebunrejo Genteng - Saiful Anwar (Sekolah Tinggi Ilmu Tarbiyah (STIT) Aqidah Usymuni, 2022)
AbstractMotivation is the powerful part of learning process for studying English. By this way, students will be more diligent to go to school and engage with the subject. The purpose of this research to reveal students’ motivation in studying English. The data analysis is utilized in this research is qualitative. This method is to reveal some information that collected from questionnaire given to students. Here, there are 40 students are asked some questions. The result of this study that students have answer the questionnaire varies greatly. The top of average percentage of the choice is neutral then followed with agree. The residue are disagree, strongly agree and strongly disagree sequentially. It means some students still hesitant to say agree or disagree about the their motivation in studying English.Keywords: motivation, students’ motivation, studying English